ELT in Nepal: Changing Teacher’s Role in the Present Context - Raju Parajuli (Prāgyik Prabāha, 2024)
This reflective paper highlights English Language Teaching (ELT) practices in Nepal, focusing on various context and dilemmas such as choosing between monolingual or multilingual approaches, using local versus international materials, and selecting authentic versus inauthentic sources. It also examines the use of textbooks written by native or non-native writers and addressed obstacles and coping strategies involved. Additionally, the reflection discusses the major roles of English teachers in Nepal as a teacher, a researcher and a practitioner. ELT in Nepal has gone significant changes mirroring global shifts in ELT trends and practices. These changes include evolving attitude towards ELT, shifting goals of ELT, new teaching methods, updated curriculum design, revised teaching content and assessment, changes in medium of instruction, changing roles of teachers. Despite some ongoing confusions, ELT movement is progressing smoothly. This reflection is based on a review of relevant articles on ELT in Nepal and my personal experience as an EFL teacher in Nepal for more than18 years.